Analysis of the Phillips Curve Theory in Controlling Inflation and Unemployment in the AJITIP Country - Wahyu Indah Sari; Rowiyah Asengbaramae (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to analyze the optimization of monetary policy and fiscal policy (current policies) in stabilizing the economy, precisely in overcoming the unemployment rate during the pandemic in the 6 lowest unemployment countries. Where monetary variables (Money Supply, Exchange Rate and Real Interest Rate), fiscal policy (Government spending), and economic stability (Inflation, GDP, and Wages). This study uses secondary data or time series, namely from 2008 to 2020. The data analysis model in this study is the ARDL Vector Panel model. The results of the IRF analysis showed that the stability of the variable response was formed in the 8th period or medium term and the 15th or long-term period, where the response of other variables to changes in one variable showed variations both from positive to negative responses and vice versa, and there were variables whose responses remained positive to negative from short to long-term. The results of the FEVD analysis show leading indicators as operational targets. Then the results of the ARDL Panel analysis show that in terms of the Inflation Panel, the Amount of Money Supply, Interest Rates, Gross Domestic Product, Government Expenditure, Exchange Rates, and Wages are able to maintain economic stability, precisely at the unemployment rate in the 6 lowest unemployment countries, in the short and long term.